Modifikasi Algoritme J-Bit Encoding untuk Meningkatkan Rasio Kompresi - Johanes K.M. Lobang; Pranowo; Suyoto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
J-bit encoding is a lossless data compression algorithm that manipulates each bit of file data in order to minimize the size by dividing data into two outputs and combining data into two outputs. This research proposes a modification of the J-bit Encoding algorithm by eliminating zero and one symbols of the first output. As a result, the first output will contain the original data without zero and one symbols and the second output will contain the value of two bits that describe the position of zero, one, and byte besides zero and one. The two algorithms are compared by testing four scheme combination algorithms, which are (i) Burrows-Wheeler transformation, Move to Front, J-Bit Encoding, and arithmetic coding, (ii) Burrows-Wheeler transformation, Move to Front, modification of the J-bit Encoding, and arithmetic coding, (iii) Burrows-Wheeler transformation, Move One From Front, J-Bit encoding, and arithmetic coding, (iv) Burrows-Wheeler transformation, Move One From Front, modification of the J-bit Encoding, and arithmetic coding. By using the Calgary Corpus and Canterbury Corpus data sets, the test results show that the best compression ratio is obtained by using a second scheme on average. On the other hand, by using four image files, the test results show that the best compression ratio is obtained by using a fourth scheme on average.